Plastics : microstructure and engineering applications - Mills, N. J. (Edward Arnold, 1993)
This book is intended for students of Engineering or Materials Science degree courses, and for scientists and engineers who require an introduction to the properties and applications of plastics. Emphasis is placed on the mechanical design of plastics products and on explaining physical properties in terms of the microstructure.
Previous edition: 1986.
Keywords: Plastics.; elektronické knihy; electronic books